MRI correlates to histopathological data in oral tongue squamous cell carcinoma diagnostics. (4th March 2021) - Huopainen, Piia; Jouhi, Lauri; Hagstrom, Jaana; Apajalahti, Satu
Abstract: Objectives: The purpose of this study was to compare magnetic resonance imaging (MRI) maximum tumor diameter and depth of invasion with histopathology in oral tongue squamous cell carcinoma (OTSCC) patients in our Institute. Another objective was to compare recorded nodal status between MRI and histology. Material and methods: MRI and pathological records of 45 patients diagnosed with T1–T3 OTSCC were reviewed retrospectively. Maximum tumor diameter and depth of invasion were measured and rechecked by oral radiologist and pathologist. Nodal status was recorded from both MRI and histopathology. Correlation analyses were performed using Pearson's correlation. Results: Both maximum tumor diameter and depth of invasion correlated significantly between MRI and histology ( ρ = 0.874, p < .001; ρ = 0.898, p < .001). Significant correlation was found between MRI and pathological dimensions in the MRI-based T-staged subgroups of T2 and T3 but not in T1. MRI sensitivity for detecting pathologically positive nodes was 60%. MRI specificity for detecting pathologically negative nodes was 83%. Moderate correlation was found between MRI and histological nodal status ( ρ = 0.44, p = .003). Conclusions: MRI tumor dimensions correlate with histopathological data in OTSCC. Based on our Finnish patient material and results, MRI serves as an accurate tool in supporting OTSCC patient treatment in our Institute.